2017
DOI: 10.5604/01.3001.0010.1018
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of D-dimer in diagnosis and prediction of venous thromboembolism in patients with abdominal malignancy

Abstract: The concentration of D-dimer is often elevated in patients with active cancer, but is not a sufficient criterion for diagnosis of VTE. The concentration of D-dimer before surgery does not determine the risk of postoperative thromboembolic complications. This is undoubtedly related to the widespread use of effective thromboprophylaxis. According to the literature, ultrasound is the optimum method for detection of VTE in surgically treated cancer patients. The effect of cancer stage on the value of D-dimer is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…D-dimer is the cleavage product of cross-linked fibrin that is formed by activation of the coagulation system, which signals hyperfibrinolysis in response to clot activation and fibrin formation (1). Elevated levels of D-dimer have been detected in patients exhibiting diffuse intravascular coagulation (2), vascular occlusion crisis in sickle cell disease (3), thromboembolic events (4,5) and myocardial infarction (6). D-dimer is a widely used biomarker for indicating the activation of coagulation and fibrinolysis (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…D-dimer is the cleavage product of cross-linked fibrin that is formed by activation of the coagulation system, which signals hyperfibrinolysis in response to clot activation and fibrin formation (1). Elevated levels of D-dimer have been detected in patients exhibiting diffuse intravascular coagulation (2), vascular occlusion crisis in sickle cell disease (3), thromboembolic events (4,5) and myocardial infarction (6). D-dimer is a widely used biomarker for indicating the activation of coagulation and fibrinolysis (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…FIB and D-dimer are speci c indicators of hypercoagulability. Hypercoagulability in patients with malignant tumors can promote the formation of tumor thrombi and cause secondary hyper brinolysis [6]. FIB is the main coagulation factor in plasma, and its normal concentration is about 2 to 4 g/L [7].…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer is a fibrin degradation product, and abnormal plasma D-dimer levels have been detected in patients with thromboembolic events [ 5 , 6 ], myocardial infarction [ 7 ], infection [ 8 ], autoimmune diseases [ 9 ], and various carcinomas [ 10 13 ]. Recent studies further showed that elevated plasma D-dimer levels can predict poor prognosis in patients with liver diseases [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to establish an objective, accurate, and simple prognostic model that can identify high-risk patients and help guide clinicians when adjusting treatment strategies. D-dimer is a fibrin degradation product, and abnormal plasma D-dimer levels have been detected in patients with thromboembolic events [5,6], myocardial infarction [7], infection [8], autoimmune diseases [9], and various carcinomas [10][11][12][13]. Recent studies further showed that elevated plasma D-dimer levels can predict poor prognosis in patients with liver diseases [14][15][16].…”
Section: Introductionmentioning
confidence: 99%